Nutritional Deficiencies and Food Insecurity Among HIV-infected Children in Tanzania - Chelsea E. Modlin, BA; Helga Naburi, MD; Kristy M. Hendricks, ScD, RD; Goodluck Lyatuu, MD; Josphine Kimaro, RD; Lisa V. Adams, MD; Paul E. Palumbo, MD; C. Fordham von Reyn, MD (Global Health and Education Projects, Inc., 2014)
Background: Poor nutrition has been associated with impaired immunity and accelerated disease progression in HIV- infected children. The aim of this study was to quantify the levels of nutrient intake in HIV-infected children and compare these to standard recommendations. Methods: We surveyed HIV-infected Tanzanian children enrolled in a pediatric care program that provided routine nutritional counseling and vitamin supplementation. We obtained anthropometric measurements and determined 24-hour macronutrient and micronutrient intakes and food insecurity. Values were compared to recommended nutrient intakes based on age and gender. Results: We interviewed 48 pairs of children and their caregiver(s). The age of the child ranged from 2-14 years; median age 6 and 60% female. The median weight-for-height z-score for children ≤ 5 years was 0.69 and BMI-for-age z-scores for children >5 was -0.84. Macronutrient evaluation showed that 29 (60%) children were deficient in dietary intake of energy; deficiency was more common in older children (p=0.004). Micronutrient evaluation shows that over half of study subjects were deficient in dietary intake of vitamin A, vitamin D, vitamin E, thiamine, riboflavin, niacin, folate, vitamin B12, and calcium. Food insecurity was reported by 20 (58%) caregivers. Conclusions and Public Health Implications: The diets of many HIV-infected children at a specialized treatment center in Tanzania do not meet recommended levels of macro- and micro-nutrients. Food insecurity was a contributory factor. Enhanced dietary counseling and provision of macro- and micro-nutrient supplements will be necessary to achieve optimal nutrition for most HIV-infected children in resource-poor regions.